Spatial variability characteristics of soil heavy metals in the cropland and its pollution source identification around the contaminated sites - LI Haiguang; SHI Jiachun; WU Jianjun (浙江大学学报. 农业与生命科学版)
The pollution of heavy metal is increasingly concerned, especially the soil heavy metals pollution around the contaminated sites. Many researchers have reported a significant increase of heavy metal in the surface soil. However, few reports have been found in the literature about soil heavy metal spatial distribution and source identification around contaminated sites. Therefore, this study has the aim of elucidating the spatial distribution and source identification of soil heavy metals in croplands near two contaminated sites. Our specific objectives were to examine the spatial dependency and the variation mechanism of heavy metals in soils, to map the spatial distribution and risk assessment of soil heavy metals, and to identify the main sources of soil heavy metal pollution.The surface soil (0-20 cm) and subsurface soil (20-40 cm) were collected from nearby fields of a battery plant (F1) and a thermal power plant (F2) in the north of Zhejiang Province. The concentrations of soil mercury (Hg), cadmium (Cd), lead (Pb), zinc (Zn), copper (Cu), and nickel (Ni) in these two typical contaminated sites were determined and the spatial distribution patterns and pollution source of the heavy metals were analyzed using Geographic Information System (GIS) and geostatistical methods. Based on the type Ⅱ limit of “Environmental Quality Standard for Soils” (GB15618 1995), the single factor method and Nemerow index method were used to assess the comprehensive pollution risks of the soil heavy metals around the contaminated sites. Inverse distance weighted interpolation (IDW) was used to simulate the pollution risk and spatial distribution and the source identification of these heavy metal pollution.Results showed there was a serious soil heavy metal pollution problem around contaminated sites, with Cd concentrations in 80.77% of the surface soil samples exceeded the type Ⅱ limit (Cd>0.3 mg/kg) of GB15618—1995. Hg concentrations in 3.85% of the surface soil samples exceeded the type Ⅱ limit. Nemerow index method assessment results showed that there were 25 soil samples exceeded the standard, with overproof rate of 48.08%. Based on the Technical Specification for Soil Environmental Monitoring, the maximum index value was 3.13, which exhibited heavy pollution. Particularly in nearby contaminated site F1, soil Cd and Pb pollution were serious problems in the soils, with Cd concentration in 91% of the surface soil samples exceeded the type Ⅱ limit (Cd>0.3 mg/kg) of GB15618—1995, and the maximum surface soil Cd concentration was 3.3 mg/kg. The soil Pb pollution was also the potential problem even then its concentration was not exceeded the type Ⅱ limit. The maximum surface soil Pb concentration was 123.67 mg/kg, and the mean surface soil Pb concentration was 58.69 mg/kg. While the surface soil Cd and Pb concentrations were significantly higher than the subsurface soil. At the nearby contaminated site F2, soil Cd and Hg pollution were serious problems in the soils. Cd concentrations in 63% of the surface soil samples, and Hg concentrations in 11% of the surface soil samples were higher than the type II limit (Cd> 0.3 mg/kg, Hg>0.3 mg/kg) of GB15618—1995. The maximum surface soil Cd concentration was 0.71 mg/kg. The mean surface soil Hg concentration was 0.214 mg/kg. Cd and Pb concentrations in the surface soil samples from F1 had similar spatial distribution patterns and the concentrations reduced with farther distance away from F1, and they were significantly higher than those in the corresponding subsurface soils. These results indicated that pollution of soil heavy metals (Cd and Pb) was mainly caused by external pollution, and F1 was the most probable pollution source. The battery plant can discharge Cd and Pb into environment. At the contaminated site F2, the heavy metal concentrations in some soil samples were higher than the type Ⅱ limit (Cd >0.3 mg/kg) of GB15618—1995. The mean surface soil Hg concentration was significantly (P<0.01) higher than that of the subsurface soil. These results indicated that soil heavy metal Hg pollution at site F2 was mainly caused by external pollution from the thermal power plant and the contaminated site F2 was one of the pollution sources.In conclusion, soil heavy metal pollution is a serious problem in the study area around the contaminated sites. The pollution of surface soil by Cd and Pb at the nearby site F1 and the pollution of surface soil by Hg and Cd at the nearby site F2 mainly comes from external pollution sources, the increase of surface soil Cd and Pb concentrations around site F1 is most likely caused by the contaminated site F1. Soil pollution by Cd, Pb and Hg of nearby fields is closely related with the contaminated sites F1 and F2, thus much more attention should be given to the prevention of the heavy metal pollution.